Approaches to building indices for the program-oriented development of settlements in the Ukrainian context - Maxym Serhiyovych Filiak; Yuliia Yuzefivna Filiak (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2018)
The focus of this study is to present an overview of Ukrainian scientific approaches to the development of monitoring and evaluation technical components, namely matrices, models, indicators and indices used in implementation of program-oriented approach to socio-economic development of settlements. The article describes scientific developments from two main fields (economic development and social development) and is grounded on the authors’ previous research, to describe the main types of groups indicators of sustainable socio-economic development for Ukrainian settlements. The need for the study is pertinent given the absence of uniformity to approaches and the need for the research to develop practically applicable monitoring tools for the research.